Interaction of Muslim with Non Muslim (Portrait of Conflict and Its Resolution with Jews of Bani Nadhir) | تعامل المسلم مع غير المسلم (صورة الصراع وحله مع يهود بني النضير) - Sahabuddin, Sahabuddin; Wibowo, Waskito; Hamood, Faisal (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
The topic of interfaith relations has become a global discourse and has attracted the attention of many academics, especially regarding the relationship between Muslims and non-Muslims, specifically Jews in this study. Judaism has a long history with Muslims. The fluctuations in relations between the two parties have continued to occur, reaching their peak in the possession of land in Palestine in this modern era. The purpose of this study is to determine the image of Islamic relations in dealing with Jews based on the books of Sahih al-Bukhari and Sahih Muslim, as well as their contemporary context. The method used for data collection is the library research method. The data analysis technique employed in this study involved descriptive, analytical, and inductive approaches. The research findings indicate that there are 47 hadith topics in the Sahihayn that mention the words "Judaism," "Qurayza," "Qaynuqa'," and "Nadir." However, only 29 of these hadiths describe interactions between Muslims and Jews. In the Sahihayn, the forms of interaction between Muslims and Jews include cooperation, competition, and conflict. Examples of cooperative interactions include the hadith about the Jews of Khaybar working on the land, the Prophet pledging his armor to a Jew, and Ali ibn Abi Talib making a dowry ring for Fatimah from a Jew of Banu Qaynuqa'.